Discrimination of same-sex marriages in the European Union - Zolotuhina, Karīna (Riga Graduate School of Law, 2022)
Protection of human rights and fundamental freedoms lies at the heart of the European Union’s values and objectives. The non-discrimination law is enshrined by numerous statutes and treaties and stays one of the core principles of the Union. Nonetheless, the LGBT community still faces various forms of discrimination and inequality in different fields of life. Same-sex marriages are a new phenomenon that is still evolving, therefore legal protection of sexual minority groups and their family life is especially concerning in the modern days. The purpose of this thesis is to present an in-depth review of EU legislation and jurisprudence on the prohibition of discrimination against same-sex married couples. The interdisciplinary approach of the thesis is to be demonstrated in the examination of the European Union’s labor market.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Discrimination; Same-sex marriage; The European Union; LGBT rights